Chapter Welfare and demography in the time of Malthus. Regional and local variations in poor relief and population developments in Flanders, c. 1750-1810 - Devos, Isabelle (Datini Studies in Economic History, 2020)
Flanders represents a particularly interesting region for research that aims to investigate the development of socio-economic inequalities at the local and regional level. The relationship between and effects of structural socio-economic characteristics on the one hand and micro-level variations on the other hand remain unclear. The data collected by the STREAM project (streamproject.ugent.be) together with its tailored geographical information system (GIS) allow us to explore these relationships for the rural parishes of early modern Flanders. In this chapter we examine spatial patterns in poor relief and demographic behaviour and how these were interrelated.